2013
DOI: 10.17645/si.v1i1.109
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Barriers to Women's Agency in Domestic Violence: The Tensions between Women's Personal Experiences and Systemic Responses

Abstract: Despite advances in knowledge and understanding about the impacts of domestic violence on women's lives, global research on violence against women shows there is a need for research that not only places women centre stage in research praxis, but also that involves them more collaboratively in genuine dialogue about their experiences, including their agentic stances. This is especially the case for marginalised and socially excluded women victims of domestic violence, such as those who are not known or do not p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…This remains the case despite observations regarding methodological limitations in the dominant PQ research programme. For example, it has been argued that a fuller qualitative account of the intricacies of DVA victim experience remains elusive not least due to a serious participant recruitment problem; only victims with sufficient confidence to share their sensitive experiences of DVA for the purposes of a research interview will typically volunteer (Aldridge, 2013). This problem is, moreover, likely to be amplified when using focus groups.…”
Section: Approaches To Qualitative Research In Dvamentioning
confidence: 99%
“…This remains the case despite observations regarding methodological limitations in the dominant PQ research programme. For example, it has been argued that a fuller qualitative account of the intricacies of DVA victim experience remains elusive not least due to a serious participant recruitment problem; only victims with sufficient confidence to share their sensitive experiences of DVA for the purposes of a research interview will typically volunteer (Aldridge, 2013). This problem is, moreover, likely to be amplified when using focus groups.…”
Section: Approaches To Qualitative Research In Dvamentioning
confidence: 99%
“…En el ámbito de la investigación psicosocial, la indagación narrativa se ha empleado para trabajar la auto-etnografía con trabajadoras sexuales (Smith, 2015), promover la reflexión con personas que viven en ambientes vulnerables (Copes, Tchoula, Brookman, & Ragland, 2018), o acceder a la experiencia de personas sin hogar en situaciones de adicción para proponer mejoras en la atención primaria (Sestito et al, 2017). Se ha utilizado también para dar voz a las mujeres que han sufrido violencia de género, involucrarlas en la investigación y darles un papel activo en el proceso (Aldridge, 2013).…”
Section: La Indagación Narrativa Visualunclassified
“…One of the outcomes for survivors like Tula is that the inequalities in their lives, that both contribute to and help sustain the public myth and private pain of DVA, are also overlooked as critical indicators in the risk to women of DVA victimization and its perpetuation. Decades of feminist research, politics, and activism have shown us that women’s inequality (economically, politically, their access to services, and so on) also makes them more likely to become trapped in violent and abusive relationships (see, for example, Aldridge, 2013; Nixon & Humphreys, 2010). Underlining this eternal return argument—inequality = victimization = inequality—many commentators argue that it is also “coercive controlling violence” (Hester et al, 2017) in intimate relationships that demonstrates, reinforces, and helps to perpetuate women’s inequality in their own lives and in society more broadly.…”
Section: Reinforcing Dva Myths and Women’s Inequalitiesmentioning
confidence: 99%
“…For many women, this situation has only worsened since the economic crash of 2008; in the United Kingdom, for example, this has also occurred as a consequence of more than a decade of austerity that has led to pernicious changes to the benefits system and sweeping cuts to essential DVA services. Research conducted in the United Kingdom by the Guardian newspaper in 2018 showed that local council funding for women’s refuges alone had been cut by just under £7 million since 2010 (Grierson, 2018; see also Aldridge, 2013). McRobie (2013, p. 1) argues that collaterally more than 10 years of austerity in the United Kingdom has resulted not only in a lack of support services for women victims—survivors of DVA, but also to an increase in DVA prevalence.…”
Section: The Continuum Of Women’s Dva Experiencesmentioning
confidence: 99%
See 1 more Smart Citation